Photodegradation behavior of different polyurethane: A comparison study of foam and leather - Linping Shi; Zhimin Gong; Minjie Xie; Wen Shao; Houru Cheng; Shixiang Gao (Journal of Environmental Sciences, 2026)

A simulation-optimization approach based on the compound eutrophication index to identify multi-nutrient allocated load - Yanqun Yang; Keqiang Li; Shengkang Liang; Guohong Lin; Cheng Liu; Jixin Li; Linping Xie; Yanbin Li; Xiulin Wang (Science of The Total Environment, 2024)

Photodynamic amplified immune checkpoint-blockade therapy of self-delivery bioregulator via epigenetic reprogramming - Linping Zhao; Chuyu Huang; Rongrong Zheng; Xiaona Rao; Renjiang Kong; Runtian Guan; Zuxiao Chen; Xiyong Yu; Hong Cheng; Shiying Li (Chemical Engineering Journal, 2023)

Investigation of VOC characteristics, source analysis, and chemical conversions in a typical petrochemical area through 1-year monitoring and emission inventory - Guimei Qin; Song Gao; Qingyan Fu; Shuang Fu; Haohao Jia; Qingrui Zeng; Linping Fan; Huarui Ren; Jinping Cheng (Environmental Science and Pollution Research, 2022)

New insights into Human Hematopoietic Stem and Progenitor Cells via Single-Cell Omics - Yawen Zhang; Yaojin Huang; Linping Hu; Tao Cheng (Stem Cell Reviews and Reports, 2022)
Residing at the apex of the hematopoietic hierarchy, hematopoietic stem and progenitor cells (HSPCs) give rise to all mature blood cells. In the last decade, significant progress has been made in single-cell RNA sequencing as well as multi-omics technologies that have facilitated elucidation of the heterogeneity of previously defined human HSPCs. From the embryonic stage through the adult stage to aging, single-cell studies have enabled us to trace the origins of hematopoietic stem cells (HSCs), demonstrating different hematopoietic differentiation during development, as well as identifying novel cell populations. In both hematological benign diseases and malignancies, single-cell omics technologies have begun to reveal tissue heterogeneity and have permitted mapping of microenvironmental ecosystems and tracking of cell subclones, thereby greatly broadening our understanding of disease development. Furthermore, advances have also been made in elucidating the molecular mechanisms for relapse and identifying therapeutic targets of hematological disorders and other non-hematological diseases. Extensive exploration of hematopoiesis at the single-cell level may thus have great potential for broad clinical applications of HSPCs, as well as disease prognosis. Graphical abstract

Expression Profiles of SIRT1 and APP Genes in Human Neuroblastoma SK-N-SH Cells Treated with Two Epigenetic Agents - Yaping Hou; Fanghua Wang; Linping Cheng; Tao Luo; Jie Xu; Huaqiao Wang (Neuroscience Bulletin, 2016)